Environmental disclosure of healthcare waste in public university hospitals in Brazil: diagnosis and proposal of a disclosure model aimed at transparency and sustainability - Anjos, Juliana dos; Rosa, Fabrícia Silva da (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: Propose an environmental disclosure model for healthcare waste aimed at public university hospitals in Brazil. Methodology: The research, of a descriptive nature, employed content analysis of reports published by university hospitals and Brazil’s top hospitals. Data collection was conducted by accessing the hospitals' websites to download the latest report published by each institution. After identifying the reports, all were analyzed according to the categories and items of the research instrument, with scores ranging from 0 (when the item was not disclosed) to 3 (when the item was disclosed with detailed information). Results: Based on the results, an HCW environmental disclosure model was developed for public university hospitals, structured into three categories: (1) Senior Management Approach (4 items), which address waste management strategies and practices; (2) Waste Management Activities (8 items), which details actions for managing and reducing HCW production; and (3)Waste Management Performance (14 items), which assesses monitoring, related incidents, and implemented changes in HCW management. Contributions of the Study: This research contributes to the literature by expanding knowledge on healthcare waste in public university hospitals in Brazil. Additionally, it has significant practical implications. Public university hospitals can use the proposed model to enhance their waste management disclosure, aligning with sustainability and transparency principles. The model can also be adopted by regulatory bodies to standardize HCW disclosure in Brazilian hospitals, providing a framework for these public institutions to implement in their reporting practices.